Kopling Oksidatif Eugenol Menggunakan Ekstrak Enzim Peroksidase dari Akar Tanaman Sawi Hijau serta Uji Bioaktivitasnya - Ardiansah, Bayu; Cahyana, Antonius Herry; Suwarso, Wahyudi Priyono; Maryana, Rianti; Merly, Siti (ALCHEMY, 2017)
Peroxidase has been successfully extracted and partially purified from Brassica juncea L. Czern root with protein content and specific activity of 0.747 mg/mL and 0.244 U/mg, respectively. Then, it was applied as biocatalyst for green oxidative coupling reaction of eugenol to produce an orange crystal, dimeric form of eugenol (84% yield). Structure elucidation was done by using FTIR, UV-Vis and GC-MS instruments. The optical activity of dimeric eugenol was found to have Ra-configuration. Furthermore, biological activity of the product as antioxidant has been evaluated resulting in IC50 values of 32.14 and 42.43 ppm for dimeric and monomeric eugenol, respectively.